Modified rotatory instruments for transphenoidal surgery: technical note - Marino Jr,Raul (1979)
A series of modified gyratory bayonets instruments is described. They have the advantage to allow any adjustable position within a 360° rotation angle, during the various surgical steps of transphenoidal surgery, thus keeping the surgeon's hand always at the same position.